The Role of Education on Human Dignity: Fostering Peace and Diminishing Violence - Petra Kleindienst (Religions, 2024)
The concept of human dignity postulates that every individual inherently possesses intrinsic worth. This means that upholding human dignity demands an end to war and violence. Rooted in Catholic social teachings, human life is sacred, and the dignity of the human being is the foundation of a moral vision for society. This becomes instrumental in educating students about the imperative nature of respect, empathy and compassion towards all, irrespective of sociocultural backgrounds and individual beliefs. Given the profound implications held by the concept of human dignity, through their influence on their students, Catholic educational institutions can wield substantial influence in fostering peacebuilding initiatives and mitigating conflict. This research article presents a comparative study between California and Slovenia, highlighting variations in the autonomy of Catholic high schools in terms of teaching and curriculum development and implementation. Qualitative research into private Catholic high schools in these two states shows that those with greater autonomy tend to foster a more comprehensive grasp of human dignity. These schools also demonstrate students’ enhanced ability to swiftly detect violations of human dignity, even when such breaches are not immediately evident. These observations emphasise the crucial role Catholic educational settings thereby play in the realm of peacebuilding and conflict deterrence, underscoring the need to embed a profound comprehension of human dignity in the educational framework.